The Implementation of Islamic Educational Values in the Qur’an, Surah Al-Baqarah Verses 30–39, among Seventh-Grade Students at MTs Ma’arif NU Banjarsari, Windusari, Magelang - Andi Astowo; Mohammad Imam Rosyadi; Trimoyo, Trimoyo; Nana Prihapsari; Dina Nurul Lita (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2024)
The purpose of this study is to describe the educational values contained in the Qur’an, Surah Al-Baqarah verses 30–39, as well as their implementation among seventh-grade students at MTs Ma’arif NU Banjarsari, Windusari, Magelang, during the academic year. This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The findings indicate that the educational values embedded in the Qur’an, Surah Al-Baqarah verses 30–39, include values of aqidah (faith), sharia, akhlaq (morality), and ibadah (worship). The implementation of these values is realized through various religious activities, such as congregational Dhuha prayer, RTQ, muroja’ah, congregational Dhuhr prayer, istighosah, muhadharah, Qur’anic recitation (tilawah), and routine mujahadah. The study concludes that the madrasah has successfully integrated Qur’anic values into the school culture as a means of shaping students’ character.